ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFFECTIVE TAX RATE PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2013 (Students' Journal of Accounting and Banking, 2015)
This study aims to analyze of factors that affect the effective tax rate on banking companies listed on the stock exchange Indonesia 2010-2013. The population in this study is a banking company that is listed on the stock exchange Indonesia 2010-2013. The sampling technique using purposive sampling method. Hypothesis testing using multiple linear regression analysis with the Statistical Product and Service Solutions. Hypothesis testing results prove that the institusional investors significant positive effect on effective tax rate. Independent commisioner significant negative effect on effective tax rate. Debt structure, profitability, and size is not a significant negative effect on effective tax rate.Keywords: Effective Tax Rate, Institutional Investors, Independent Commissioner, Debt Structure, Profitability, Size